A Sociological Analysis of Civil Society Success in International Development Project (Global Journal of Human-Social Science, 2013)
This paper examines the various determinants of civil society or NGOs success in the international development project Civil society is a broader concept that consists of all the social groups and social relationships in which humans are embebbed including family community social movements religious organizations schools ethnic groups clubs professional associations PTAs etc It refers to the quality of people s social life which includes safety improved healthcare mortality civility respect for diversity and so forth Several scholars have identified various determinants for civil society success notably in developing nations These include NGOs intermediary role serving as a source for feed-back and integration and cooperation among competing organizations Others attribute the success to accountability collaboration with international activist groups diffusion of ideas through rapid communication carried out and advanced by certain rooted cosmopolitans and availability of funds from international donors The article examines scholars centripetal and centrifugal on the subject matter and highlights some implications It concludes that civil society contributes to the international development project through ensuring democracy by mobilizing the public creating awareness political participation advocacy campaigns and struggle for political rights It finally posits that the determinants for civil society NGO success in international development project are multidimensional advocating for a development model that recognizes the role of religious organizations as civil society actors in order to have a meaningful compatible and sustainable development model
Keywords: civil society; NGOs; international development; determinants; success; Africa